2017
DOI: 10.1007/s12630-017-1008-8
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent analgesic effectiveness between perineural and intravenous dexamethasone as adjuvants for peripheral nerve blockade: a systematic review and meta-analysis

Abstract: The results of our meta-analysis suggest that PN and IV dexamethasone provide equivalent analgesic benefits and have similar safety profiles, when used as adjuvants, for peripheral nerve blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 44 publications
(199 reference statements)
1
21
1
3
Order By: Relevance
“…A meta-analysis by Choi et al showed that the use of perineural dexamethasone significantly prolonged the duration of analgesia approximately by 6 hours compared to the use of IV dexamethasone. A recent meta-analysis by Hussein et al showed that irrespective of dose, the use of perineural dexamethasone does not appear to provide a significant incremental benefit to the pain score, duration of analgesia or motor blockade, and cumulative opioid consumption when compared to the use of IV dexamethasone at a 24-hour follow-up ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis by Choi et al showed that the use of perineural dexamethasone significantly prolonged the duration of analgesia approximately by 6 hours compared to the use of IV dexamethasone. A recent meta-analysis by Hussein et al showed that irrespective of dose, the use of perineural dexamethasone does not appear to provide a significant incremental benefit to the pain score, duration of analgesia or motor blockade, and cumulative opioid consumption when compared to the use of IV dexamethasone at a 24-hour follow-up ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests adding dexamethasone cautiously in diabetic patients although this hypothesis must be confirmed by further research in this patient population. Williams et al evaluated the toxicity of perineural adjuvants to ropivacaine in an animal model and proved the administration of supratherapeutic doses of dexamethasone for two hours did not appear to cause neuronal cell death ( 12 ). Future studies should focus on evaluating the dose-dependent analgesic effects of perineural or interfascial dexamethasone addition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study also showed perineural and intravenous dexamethasone has equivalent analgesic benefits and similar safety profiles when used an adjuvant to peripheral nerve block (13).…”
Section: Incidence Of Postoperative Complicationsmentioning
confidence: 93%
“…route. 22 Surprisingly, in a recent study of healthy volunteers, addition of perineural or i.v. dexamethasone to ulnar nerve block with ropivacaine did not show any significant benefits over saline.…”
Section: Comparison Of the Perineural And Systemic Routes Of Adjunct mentioning
confidence: 98%